Modernisasi Pesantren Menuju Sekolah Unggul: Modernization of Islamic Boarding Schools Towards Excellent Schools - Istikomah, Istikomah (Universitas Muhammadiyah Sidoarjo, 2017)
Pesantren as an Islamic educational institution which was first established in Indonesia has strong tradition root in society. At the beginning, it was established by the muslim community independently, it was nonformal and taught only religious material. However, it is now continuing to renew the pattern of formal education in the form of schools or madrasa with the standard government curriculum. The existence of pesantren is no longer considered as second class of educational institution, and not qualified, but as a prestigious educational institution because it has established schools or madrasah that are managed professionally, so its ouput and outcome have superior quality compared to general school or madrasah. Thus the existence of pesantren is now a part of the national education system that graduation has a dual advantages of the mastery of science and religion in a balanced way